POLEMIK PASAL 3 UU NO. 31 TAHUN 1999 TENTANG TIPIKOR MENGENAI UNSUR NIAT JAHAT DAN MEMPERKAYA DIRI BAGI PELAKU TINDAK PIDANA KORUPSI - Berlian Tarigan (JURNAL JUSTIQA, 2020)
The Constitutional Court (MK) has received a request for judicial review of Article 2 and Article 3 of Law No. 31 of 1999 concerning Eradication of Criminal Acts of Corruption (Corruption Act) as amended by UUNo. 20 of 2001, through Decision No. 25 / PUU-XIV / 2016. In that decision, the Constitutional Court stated that the phrase "can" in Article 2 paragraph (1) and Article 3 of the Corruption as already amended by Law No. 20 of 2001 contrary to the 1945 Constitution and has no binding legal force. Then it becomesa legal issue whether the MKNo Decision is made. 25 / PUUXIV / 2016 will be a solutionto the problem of applying Article 3 of Law no. 31 of 1999 or does the reverse cause newlegal problems? The evil intention (mens rea) in the form of intent in Article 2 of thePTPK Law above is not made clearly, but from the sentence "... unlawfully commits actsof enriching oneself or another person or a corporation ...", then the form of intent isincluded "with intent or with the aim ". This implied that PMH was carried out with theintent or purpose of enriching oneself or another person or a corporation. WhereasArticle 3 of the PTPK Law clearly and explicitly includes the words "for the purpose of"benefiting oneself or another person or a corporation. The subjective element inherent inthe mind of the maker according to article 3 is the creator's goal in carrying out the actof abusing authority and others that is to benefit oneself or another person or acorporation. definition of the element of "enriching" oneself or another person or acorporation (vide Article 2 paragraph (1) of law number 31 of 1999 jo law number 20 of2001), then a discussion of the meaning of elements with the aim of "benefiting oneself orpeople another or a corporation "(vide Article 3 of law number 31 of 1999 in conjunctionwith law number 20 of 2001), which is an alternative element so that it is not necessarywhether the perpetrators of a criminal act of corruption must enjoy the proceeds ofcorruption, because it is enough that the offender has "enriched" another person orbenefited another person.